Analisis Terhadap Kebijakan Pemanfaatan Tanah Kas Desa Di Kabupaten Sleman Daerah Istimewa Yogyakarta - Lucia Setyawahyuningtyas (JURNAL HUKUM PELITA, 2025)
The purpose of this study is to analyze the relevance of the village treasury land utilization policy in Sleman Regency, including land sales to the general public under the pretext of investment while reviewing the authority of village officials (Village Heads/Lurah) in carrying out supervision of the utilization of village treasury land in accordance with applicable laws and regulations. This study uses a qualitative method with a normative legal approach, which is an approach that emphasizes the study of written law based on laws and regulations and is relevant to existing problems and then analyzes it by identifying, classifying, and reviewing the substance of the law. The land policy of village treasury land in Sleman Regency, Special Region of Yogyakarta, gave birth to legal dualism (legal pluralism), namely national law and customary law so that the relevance in the utilization of village treasury land here is the interaction between national regulations and local wisdom which is then implemented through the Governor's Regulation and Regent's Regulation which emphasizes the utilization of village treasury land for the interests and welfare of the village community. The authority of the village apparatus (Village Head/Lurah) in carrying out supervision of the utilization of village land is through strict supervision and strict law enforcement so that there needs to be socialization of clear regulations and licensing procedures to prevent deviations